Combining the best of two worlds: highly flexible chimeric antigen receptor adaptor molecules (CAR-adaptors) for the recruitment of chimeric antigen receptor T cells - Darowski, Diana (MAbs, 2019)
Chimeric antigen receptor (CAR)-engineered T cells have a proven efficacy for the treatment of refractory hematological B cell malignancies. While often accompanied by side effects, CAR-T technology is getting more mature and will become an important treatment option for various tumor indications. In this review, we summarize emerging approaches that aim to further evolve CAR-T cell therapy based on combinations of so-called universal or modular CAR-(modCAR-)T cells, and their respective adaptor molecules (CAR-adaptors), which mediate the crosslinking between target and effector cells. The activity of such modCAR-T cells is entirely dependent on binding of the respective CAR-adaptor to both a tumor antigen and to the CAR-expressing T cell. Contrary to conventional CAR-T cells, where the immunological synapse is established by direct interaction of CAR and membrane-bound target, modCAR-T cells provide a highly flexible and customizable development of the CAR-T cell concept and offer an additional possibility to control T cell activity.